Kemampuan Pemecahan Masalah Dalam Pembelajaran Matematika Berbasis Persepsi Guru Sekolah Dasar - Maifit Hendriani; Jamaris Jamaris; Sufyarma Marsyidin (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
The research was motivated by the lack of optimal learning which focuses on developing elementary school students' Mathematical problem-solving abilities. The aim of this research is to describe problems related to the development of elementary school students' mathematical problem-solving abilities based on teachers' views. Qualitative descriptive is the method in this research with research subjects being five elementary school teachers in Padang City. The instrument used in the form of a validated questionnaire refers to four indicators, namely learning innovation (learning by problem-solving), non-routine questions, implementing problem-solving steps using metacognitive guidance techniques, and implementing learning using models. Data analysis techniques include data reduction, data presentation, and drawing conclusions. It was found that the problems faced by teachers in developing mathematical problem-solving abilities in elementary schools resulted: in (1) low students' ability to understand problems; (2) low students' self-confidence in solving problems; (3) students' thinking and analytical abilities. students' abilities are weak; (4) students are not yet accustomed to learning that develops problem-solving skills, as evidenced by students having difficulty determining what steps to take when facing problems; and (6) teachers have difficulty conditioning students who are noisy when given mathematical problems.